Pakistan : Oil and Gas Review - World Bank (Washington, DC, 2013)
Substantial progess has been made in Pakistan in the restructuring and reform of the oil and gas sectors, deregulation of prices, and privatization of selected assets. The reforms have enhanced transparency, making decisionmakers aware of the various aspects of the business. This review documents the accomplishments to date, and attempts to identify measures that merit priority attention with respect to natural gas, petroleum downstream, and macroeconomic management. The report concludes that Pakistan would benefit greatly from pursuing the reform program it initiated in 2000. The remaining measures will enable the government to unlock the full indigenous resource potential to accelerate growth and improve the welfare of the population. It would release scarce public resources from the hydrocarbon sector, which could then be mobilized for other priority needs like health and education. The reform process would be greatly facilitated through consultations with stakeholders, and using international experience in oil and gas sector reform. A competitive, largely private owned, and efficiently run oil and gas sector will deliver quality energy supplies to the consumers at realistic prices in a sustainable environment.